Phytosociological Analysis of Selected Shola Forests of the Nil Girl Fills of Western Ghats - Vidyasagaran, K.; Gopikumar, K.; Ajithkumar, M. (Indian Forester, 2004)
The present investigation was undertaken to characterize the floristic composition, structure, vegetation diversity and changes in physico-chemical properties of soil at different altitudinal zones of Shola forests in the Nilgiri hills of Western Ghat. The floristic composition revealed that the Shola forests of Brammagiri hills of Western Ghllt consist of 91 families belonging to 70 genera and 43 families. Vegetation structure showed that Cinnamomum perrottetii has highest density followed by Actinodaphne salicina and Microtrt.pis stocksii. However, highest basal area was for Ligusrtum perrottettii and Neolitzea zeylanica. In regenerating community, Actinodaphne salicina represents maximum regeneration followed by Bhesa indica. Plant diversity study indicated that Simpson’s index was 0.94 and concentration of dominance was 0.06. Investigation on physico-chemical properties of soil revealed no remarkable variation in soil properties with increasing elevation.